A Review of Molecular Mechanisms Involved in Toxicity of Nanoparticles - Javad Khalili Fard; Samira Jafari; Mohammad Ali Eghbal (Tabriz University of Medical Sciences, 2015)
In recent decades, the use of nanomaterials has received much attention in industrial and medical fields. However, some reports have mentioned adverse effects of these materials on the biological systems and cellular components. There are several major mechanisms for cytotoxicity of nanoparticles (NPs) such as physicochemical properties, contamination with toxic element, fibrous structure, high surface charge and radical species generation. In this review, a brief key mechanisms involved in toxic effect of NPs are given, followed by the in vitro toxicity assays of NPs and prooxidant effects of several NPs such as carbon nanotubes, titanium dioxide NPs, quantum dots, gold NPs and silver NPs.